2023
DOI: 10.1055/a-2022-2663
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation dose from gastrointestinal endoscopy procedures with special emphasis on eye lens doses in endoscopic retrograde cholangiopancreatography

Abstract: Background and aims Endoscopic retrograde cholangiopancreatography (ERCP) procedures may result in remarkable radiation doses to patients and staff. The aim of this prospective study was to determine occupational exposures in gastrointestinal endoscopy procedures, with a special emphasis on eye lens dose in ERCP. Methods Altogether 604 fluoroscopy-guided procedures, of which 560 were ERCPs belonging to four American Society for Gastrointestinal Endoscopy procedural complexity levels, were performed using two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Although significantly higher than in the C-ERCP group, the DAP in the EA-ERCP group is still within the lower end of the acceptable range of dose reference levels suggested by the ESGE for conventional ERCP procedures [5]. However, based on recent studies, there is probably still room for improvement to further reduce radiation exposure thanks to more stringent adherence to the ALARA principle [20,21]. The results obtained in the current study may serve as a starting point to identify DAP dose reference levels in patients with surgically altered anatomy undergoing EA-ERCP using any type of device-assisted enteroscopy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although significantly higher than in the C-ERCP group, the DAP in the EA-ERCP group is still within the lower end of the acceptable range of dose reference levels suggested by the ESGE for conventional ERCP procedures [5]. However, based on recent studies, there is probably still room for improvement to further reduce radiation exposure thanks to more stringent adherence to the ALARA principle [20,21]. The results obtained in the current study may serve as a starting point to identify DAP dose reference levels in patients with surgically altered anatomy undergoing EA-ERCP using any type of device-assisted enteroscopy.…”
Section: Discussionmentioning
confidence: 92%
“…The obtained DAP data are even at the lower end of the acceptable dose reference levels range. More recent literature data also show that these dose reference levels decrease with time over the years thanks to newer fluoroscopy machines on the one hand and the increased awareness of the risk of radiation exposure and the importance of radiation protection by the clinical staff on the other hand [20,21]. Stringent adherence to the ALARA principle may even reduce DAP dose reference levels for C-ERCP procedures to as low as 1-3 Gy*m 2 [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median KAP for ERCPs in their study was 1.83 Gy·cm 2 (IQR: 1.20–2.90 Gy·cm 2 ). Similarly, Kaasalainen et al [ 29 ] reported that the ASGE level impacted radiation exposure. They also determined higher doses for ERCPs performed for PSC indication compared to other indications.…”
Section: Discussionmentioning
confidence: 96%
“…The imaging technique used, such as fluoroscopy at different dose levels and pulse rates, acquisition of single radiographic images, or frame acquisition can impact patient radiation exposure. Additionally, factors such as the type of X-ray equipment, distance between the endoscopy and fluoroscopy monitors, anatomical location of the targeted pathology, pancreatic indication for the procedure, cannulation difficulty, experience of the endoscopist, annual volume, trainee involvement, procedural complexity, sphincterotomy, stent placement, balloon dilatation, stone extraction, and brushing have been identified as associated with increased radiation exposure in ERCP [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The degree of procedural complexity can significantly vary within the same ERCP procedure due to factors such as patient anatomy, clinical factors, pathology being treated, and disease severity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%